The atypical CDK activator RingoA/Spy1 regulates exit from quiescence in neural stem cells - Laura Gonzalez; Ana Domingo-Muelas; Pere Duart-Abadia; Marc Nuñez; Petra Mikolcevic; Elisabet Llonch; Monica Cubillos-Rojas; Begoña Cánovas; Stephen M.A. Forrow; Jose Manuel Morante-Redolat; Isabel Fariñas; Angel R. Nebreda (iScience, 2023)
Summary: In the adult mammalian brain, most neural stem cells (NSCs) are held in a reversible state of quiescence, which is essential to avoid NSC exhaustion and determine the appropriate neurogenesis rate. NSCs of the mouse adult subependymal niche provide neurons for olfactory circuits and can be found at different depths of quiescence, but very little is known on how their quiescence-to-activation transition is controlled. Here, we identify the atypical cyclin-dependent kinase (CDK) activator RingoA as a regulator of this process. We show that the expression of RingoA increases the levels of CDK activity and facilitates cell cycle entry of a subset of NSCs that divide slowly. Accordingly, RingoA-deficient mice exhibit reduced olfactory neurogenesis with an accumulation of quiescent NSCs. Our results indicate that RingoA plays an important role in setting the threshold of CDK activity required for adult NSCs to exit quiescence and may represent a dormancy regulator in adult mammalian tissues.